Determining variables that influence the phosphorus content of waste stabilization pond algae. (1st April 2018) - Sells, Matthew D.; Brown, Nicola; Shilton, Andrew N.
Abstract: Waste stabilization ponds (WSP) are one of the most common forms of wastewater treatment for smaller communities globally, but have poor phosphorus removal. It is known that WSP algae can accumulate polyphosphate within their cells in excess of that needed for cell function. If polyphosphate accumulation could be triggered at the higher range of WSP cell concentrations, phosphorus removal from domestic wastewater could be significantly improved. However, this phenomenon is sporadic and still not fully understood. With a view of building a fundamental understanding to underpin the engineering of a new phosphorus removal process, this paper examines eight previously untested variables that may influence the cellular phosphorus content of WSP biomass. Although calcium, magnesium, and potassium are key constituents of polyphosphate granules, the concentrations tested were not limiting to polyphosphate accumulation. While literature also pointed to inoculum characteristics as potentially having an impact, no significance was found in this research. Conversely, three important new triggers where identified that significantly (90% confidence) affected the cellular phosphorus content of WSP biomass. An increase in cellular phosphorus content was triggered by decreasing the organic load, or allowing the pH to increase as compared to pH control. By contrast, the presence of mixing decreased the phosphorus content of the WSP biomass. Graphical abstract: Image 1 Highlights: The effect of variables on the phosphorus (P) content of algal biomass was studied. Increasing the pH or reducing the organic load caused the P content to increase. Concentration of cations (Ca, Mg, K) had no effect on the P content. Inoculum P accumulation or biomass concentration had no effect on the P content. Increasing the mixing intensity reduced the P content of the biomass.